RELASI BUDAYA ORGANISASI DAN POLITIK TERHADAP SUKSESI REFORMASI BIROKRASI - Sinaga, Rudi Salam (Universitas Medan Area, 2012)
Bureaucratic reform requires the creation of good governance, namely the process of interaction between state institutions to the community derived from elements of civil society in order to perform the construction and establishment of good governance. In the practice to achieve Good Governance found